Emotional empathy predicting subjective well-being: undergraduate and graduate comparison - Samer Adnan Abdel Hadi; Mahmoud Fisal Al-Quraan (International Journal of Evaluation and Research in Education (IJERE), 2025)
The current study aims to determine if emotional empathy predicts subjective well-being among undergraduate and graduate students. The current quantitative investigation is based on the survey research design. Participants were students from Al Ain University’s Abu Dhabi and Al Ain campuses (n=307). Data were gathered using the multidimensional emotional empathy scale (MDEES) and the subjective well-being scale (WeBs). The study found that increasing emotional empathy resulted in enhanced subjective well-being among undergraduate and graduate students. The findings also revealed that an increase in the emotional attention component of emotional empathy is associated with a decrease in subjective well-being. The suffering component of emotional empathy makes the greatest contribution to predicting subjective well-being among undergraduate and graduate students. The component of feeling for others ranks second in terms of capacity to predict subjective well-being among undergraduate students. Positive sharing is the second most effective predictor of subjective well-being among graduate students. We discovered that there is a need to increase college students’ subjective well-being, which has a major impact on their overall well-being.